HRES Grid-Connected System Energy Management and Power Quality Improvement (International Journal of Food and Nutritional Sciences, 2021)
The grid-integrated system's top concerns right now are Power Quality issues. Hybrid Renewable electricity Sources (HRES) are essential for distributed generation to meet the demand for electricity around the world.. The Extended Search Algorithm (ESA) is employed for voltage stabilization, power loss reduction, and energy management. The results of the simulations show that the proposed converter performs better than the traditional PI controller. The MATLAB/ SIMULINK platform is used to run the simulations.Compensates harmonics and unbalances even under distorted supply voltage conditions if the load is associated at the Point of Common Coupling (PCC), which is non-linear or unbalanced and both.